(untitled) (Journal of Business and Technology (Dhaka), 2016)
In this age of innovation and globalization, interest in research on measuring and analyzing intellectual capital (IC) and determining its impact on business performance is on the rise. This study is intended to review the literature concerning the effects of implementing the Balance Scorecard (BSC) on the organizational performance of banks, with the Intellectual Capital (IC) enhancement being the mediator. Based on the literature a new comprehensive performance measurement framework for banks has been proposed. This framework can be validated through further research by integrating the interaction between BSC and IC components in the context of Bangladeshi banks by examining different banking environment i.e. nationalized, private commercial, foreign commercial and Islamic banks, as the literature shows strong deviation in measurement models depending on the nature of business. Journal of Business and Technology (Dhaka) Vol.10(2) 2015; 81-95